HUMAN FACTORS: THE PROBLEM OF MAN-MACHINE INTERACTION UNDER THE DIGITALIZATION CONDITIONS - Protasenko, Olga; Mygal, Galyna (Scientific Journal of Polonia University, 2022)
The main attribute of a modern labour paradigm is a new type of man-machine interaction – the digital ecosystem. However, despite the improvement of man-machine interaction, the human factor remains the most difficult issue in ensuring the safety of such systems. Moreover, the digitalization process complicated the problem of the human factors because it led to a decline of the human’s subjective responsibility for the actions performed because of a significant increase in the share of artificial intelligence in decision-making. As a result, the number of accidents in recent years has decreased but insignificantly. In most cases, the research methods of the human factor are focused on environmental and technical problems of the system functioning, leaving a human unattended. In this regard, the research aims at the peculiarities of human activity in the digital ecosystem. The research was carried out in two directions. The first one is the study of human needs in the digital ecosystem, due to which it was established that a person needs digital safety. This need determined the emergence of a new phenomenon – the safety culture in the digital space. The second direction is the study of the person’s resources. The study of this issue showed that the “cycle” of resources and, in particular, its balanced affects the manifestation of the “human factors” phenomenon.